(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Enzymatic saccharification (Hydrolysis) is one of the technologies to hydrolyze lignocellulosic biomass. In this study, Bangladeshi bagasse is used as feedstock for enzymatic saccharification and ethanol fermentation. Cutter mill and Mechano-chemical treatment (Ball mill) are used for pretreatment. The main objective of this study is to investigate the effect of substrate concentration, pretreatment time and enzyme concentration to enzymatic hydrolysis and ethanol fermentation. The yield of glucose from cellulose is decreased with increasing substrate concentration from 5% to 15%, but the total amount of glucose is increased with increasing substrate concentration. Sample with long pretreatment time hydrolysis easily. Ball milling pretreatment of 1 hour is the most effective on enzymatic hydrolysis which gives better sugar yield than others. Enzyme loading has significant effect on enzymatic hydrolysis. Yeast Saccharomyces cerevisiae was used to converts C6 sugar into ethanol and incubated at 30oC for 96 hours. Almost all fermentable sugar converted into ethanol within 24 hours. Key words : Enzymatic saccharification;, Lignocellulosic biomass; Ethanol; Fermentation; Mechano-chemical treatment. DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9042 BJSIR 2011; 46(3): 353-358